Roles, Conflicts, and Attachments: Motherhood in Selected Malaysian Poems - Lalitha Parasuraman; Jeslyn Sharnita Amarasekera; Seach Jin Beng (Asiatic: IIUM Journal of English Language and Literature, 2025)
Motherhood is often perceived as a unique and transformative journey, intricately linked to mothers, children, families and society. The roles expected of mothers have not changed much despite the ever-evolving societal dynamics. Asian mothers, especially in modern Malaysia are expected to juggle work and household chores and attend to the needs of their loved ones including their children, spouses, and extended family members. More often than not, this results in tremendous amounts of struggles, stress, trauma, and long-term psychological impacts on mothers because failing to perform maternal duties is never an option. Correspondingly, this study explores Malaysian poetry that depicts the intricacies of motherhood and its various aspects. Role theory, which conceptualises daily activities as performing roles that are socially constructed classifications, is applied in the analysis of six Malaysian poems, written by both female and male poets of different age groups. The representations of role playing and role taking as employed within role theory is utilised to uncover the ways in which mothers develop their concept of self accordingly. Findings highlight how poetry can unravel the connecting flow of multiple roles in motherhood that leads to conflicts, yet still result in attachment between the mother and child. The analysis reveals that a mother’s role is actually paradoxical in nature and the multiple roles, conflicts, and attachments merge together within motherhood; these entities cannot function on their own as they are all interconnected in the relationship. Both positive and negative emotions have been found to play a crucial part in leading to various types of attachments between mothers and children, which can be loving, bittersweet, or traumatic. This research has found Malaysian poetry unravels the different representations of motherhood in Malaysia whose experience is more than what meets the eye.